2021
DOI: 10.3389/fpls.2021.680376
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous 6-Benzyladenine Improves Waterlogging Tolerance in Maize Seedlings by Mitigating Oxidative Stress and Upregulating the Ascorbate-Glutathione Cycle

Abstract: The synthetic cytokinin 6-benzyladenine (6-BA) regulates plant growth and prevents the negative consequences of various forms of abiotic stress, including waterlogging in crop plants. The present study aimed to investigate the effects of exogenous 6-BA on the growth, oxidative stress, and ascorbate-glutathione (AsA-GSH) cycle system in the inbred SY-MY13 (waterlogging-resistant) and SY-XT1 (waterlogging-sensitive) seedlings of waxy corn in conditions of waterlogging stress. The results demonstrated that waterl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 124 publications
1
12
0
Order By: Relevance
“…It has been previously shown that the increased synthesis and response of cytokinins (CTKs) leads to enhanced scavenging capability of ROS. For example, the application of synthetic CTK 6‐benzyladenine (6‐BA) improved waterlogging tolerance in maize seedlings via the elimination of ROS (Wang et al, 2021). The activities of antioxidant enzymes were promoted by exogenously applied kinetin, thereby protecting tomato plants against NaCl‐induced oxidative stress (Ahanger et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…It has been previously shown that the increased synthesis and response of cytokinins (CTKs) leads to enhanced scavenging capability of ROS. For example, the application of synthetic CTK 6‐benzyladenine (6‐BA) improved waterlogging tolerance in maize seedlings via the elimination of ROS (Wang et al, 2021). The activities of antioxidant enzymes were promoted by exogenously applied kinetin, thereby protecting tomato plants against NaCl‐induced oxidative stress (Ahanger et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, APX and POD catalyze the conversion of H 2 O 2 to O 2 − (Lin et al, 2004; Salah et al, 2019), leading to the low content of H 2 O 2 accumulated in both drought and flooding stresses. Moreover, the more accumulation of ROS in flooding stress or drought stress is, the more membrane lipid peroxidation and damage membrane homeostasis are, ultimately accelerating leaf senescence and inhibiting the growth of plants (LIU et al, 2010; Wang et al, 2021). All the above give us new insights into understanding the different scavenging mechanisms of ROS and the adaptive growth mechanism of maize in response to drought and flooding stresses.…”
Section: Discussionmentioning
confidence: 99%
“…Stress responses are often associated with redox homeostasis and normally lead to a rapid and transient increase in the levels of intracellular ROS [ 57 , 58 ]. Plants have evolved an efficient ROS scavenging system to maintain redox homeostasis under stress including enzymatic components such as GSTs [ 59 , 60 ] and metabolic components such as ascorbate and glutathione, forming the ASC–GSH cycle [ 61 , 62 , 63 ]. This system ensures the efficient removal of hydrogen peroxides and lipid peroxides [ 64 ].…”
Section: Discussionmentioning
confidence: 99%